Elementos jurídicos da política agrícola no Brasil - Rossito, Flavia Donini (2015)
The study aims to understand the agricultural policy with an important legal institute of agrarian law. For the present academic study is on the basis in the public policy that the legal elements of agricultural policy are made. Is taken the agrarian policy as gender and the agricultural policy as its kind as dialogue with the theory of agrarian policy of Antonino Carlos Vivanco. This study also aims to study the contours of a new constitutional order in the formation of a contemporary agricultural policy which should be attentive not only to the rural economy, but also the adversities imposed by land and cultural diversity within the rural in the Brazil. Are studied the planning, the implementation and the control of the agricultural policy as processes governed by the law. The agricultural policy as the State action rural economy can be controlled internally by the public administration and externally by judicial control and by social control.